Psychological meaning and main causes of mobbing among children of secondary school age - Величко, Марина (Київський національний університет імені Тараса Шевченка, 2019)
The article is an analysis of the mobbing problem occurrence among children adolescents, establishing the causes of a school environment the main characteristics of the concept and finding ways to prevent mobbing. The method of studying the problem of mobbing in children in the school environment explains to us the root causes of its occurrence, reveals the very essence of its appearance, as well as the manifestations of mobbing in middle school age children from their peers.In a deeper analysis of the problem of mobbing, we identified the main aspects of preventing this phenomenon, also developed a methodological plan for the prevention of mobbing in schools, and developed and described preventive measures to prevent manifestations among middle school children for teachers and parents who have and can influence students or their children in the context of this issue. The findings of this paper reflect the state of the problem of mobbing in the current educational process in Ukraine, taking into account the actualization of its manifestations due to the large number of displaced persons, including middle-aged children, from temporarily occupied territories during the Russian armed aggression against our country. The processes taking place in our extremes and in the world are inevitable for society as a whole, and so the challenge we face requires more detailed consideration of the issue of mobbing among adolescents of schools, the urgent response to its present manifestations, and addressing these issues, specifics of personal approaches to middle school children in each case. Analyzing the problem of mobbing among children in school, especially middle school children, we have come to the conclusion that the multiplicity of influence factors determines the direction of the study of the problem and gives this problem a new special approach, taking into account many points, and obliges us to solve the problem of mobbing the school, so that it does not persecute a person who is primarily a person, in adolescence and adulthood.

Метою статті є аналіз проблеми виникнення мобінгу серед дітей підліткового віку та встановлення сутності причини його виникнення у шкільному середовищі, основних характеристик поняття, а також пошуку шляхів запобігання мобінгу.
Психологічний зміст та основні причини виникнення мобінгу серед дітей середнього шкільного віку
Keywords: мобінг; шкільне середовище; агресор; жертва; mobbing; school environment; aggressor; victim